PENGETAHUAN TERHADAP PENCEGAHAN MYOPIA DENGAN WEBINAR BERPERILAKU SEHAT SECARA DIGITAL - Hermawati, Bertakalswa; Handayani, Oktia Woro Kasmini; Indrawati, Fitri; Siyam, Nur; Tamalla, Putri Nur; Ananditya, Vika Rifti; Shanisa, laurell (Poltekkes Kemenkes Malang, 2022)
Cases of myopic visual impairment in school age children increased during the pandemic. The purpose of this study was to increase parents' knowledge of the protection of myopia health in children during a pandemic after being given an intervention. This study used a quasi experimental study approach and the design of The One Group Pretest Posttest. The population was parents with school age children between 6 until 10 years old at SD Al Huda. The sample in this study were 28 parents with school age children between 6 until 10 years old at SD Al Huda who were willing to be involved in this intervention. The method used is a lecture with a webinar using a zoom application about myopia visual impairment. The components of interventions are the definition, the classifications, the impact, the risk factors, and the protective factors of myopia. The research instrument is a questionnaire in a google form. It is given before and after the intervention. Data analysis used the Wilcoxon Rank Test. The results found an increase in the knowledge of parents on myopia health protection by 0.019